(untitled) (Journal of history, 2020)
The article based on the analysis of archival documents and statisti- cal materials the issues of cross-border cooperation between Kazakhstan and China and Mongolia at the turn of the century. An analysis of archival materials allowed highlighting issues such as information on the ethnic composition of traders, merchants, the exit site, the amount of capital. Based on statistical data shows turnover on the border, information on smuggling, the range of export and import goods. Analysis of the content of trade agreements gives an idea of the relationship of border areas.The article analyzes the key components in the context of foreign trade activi- ties such as foreign trade, migration, language training. Border regions due to its geo-economic position act as a natural «bridges» economic coopera- tion of neighboring countries; while their development is most dependent on the nature of economic and political relations at the international level, the ratio of the contact and barrier functions of the borders.